Integrasi Penerapan Akuntansi Forensik dan Audit Investigatif dalam Mendeteksi Fraud: Studi Literatur - Yudhi Prasetiyo Prasetiyo; Diky Paramitha; Etik Ipda Riyani; Faizul Mubarok (Jurnal Buana Akuntansi, 2023)
Financial scandals often occur in the business world, and many cases such as KKN (corruption, collusion, and nepotism), manipulation of financial reports, and money laundering often occur. These various kinds of issues are very good and very interesting to discuss because there are many ways that actors use to provide information that is made up of neat schemes but end up committing fraud to various parties. The purpose of this research was to find out the role of forensic accounting and investigative auditing in finding and detecting fraud through a literature review. The research process was carried out in an observational and exploratory manner using the literature review method. The population in this study is all research and studies related to the field of forensic accounting and investigative auditing in detecting fraud or fraud. The results of the study found that forensic accounting and investigative auditing are collaborative and proven in fraud detection. An investigative audit seeks to detect and reveal fraud, while forensic accounting can be a valid means of evidence in legal and litigation processes that have reached the court and trial stages in the process of disclosing fraud.